PSXII-15 Effects of poor maternal nutrition during gestation on oxidative stress in offspring muscle. (7th December 2018) - Iannitti, H; Jones, A; Hoffman, M; Pillai, S; McFadden, K; Govoni, K; Zinn, S; Reed, S
Abstract: Poor maternal nutrition decreases postnatal muscle growth, alters muscle lipid accumulation and alters metabolism. However, the mechanisms that drive these adverse effects remain poorly understood. Oxidative stress is associated with lipid and protein oxidative damage, inflammation, and metabolic function modifications, which may occur in the muscle of offspring born to ewes exposed to poor nutrition during gestation. Therefore, we hypothesized that measures of oxidative stress in offspring muscle would be increased by poor maternal nutrition during gestation. To test this, 36 multiparous ewes (25 Dorsets, 7 Shropshires, and 4 Southdowns) received diets containing 60% (restricted), 100% (control), or 140% (over) of NRC requirements for TDN from d 31 ± 1.3 of gestation until parturition. Offspring were necropsied within 24 h of birth or maintained on a control diet for 3 mo. Longissimus muscle samples were collected from each lamb and used for malondialdehyde (MDA) and protein carbonyl concentration analyses (n = 3 to 6 per maternal diet per age) to determine muscle lipid and protein oxidation, respectively. Data were analyzed for effects of maternal diet, age of the offspring, and their interaction using the glimmix procedure in SAS. There was a tendency for an effect of maternal diet on MDA concentration (P = 0.10) where offspring from over-fed ewes had greater MDA concentrations than offspring from restricted-fed ewes (over = 2.1 ± 0.13 µg/mg protein, restricted = 1.6 ± 0.15 µg/mg protein; P = 0.04). There was no effect of offspring age on MDA concentrations (P = 0.12). There was no effect of treatment or age on protein carbonyl concentrations in offspring muscle (P > 0.10). These results suggest that maternal over-nutrition during gestation may have greater effects on lipid oxidation than protein oxidation, which may contribute to poor postnatal muscle growth in offspring.